A Critical Review on the Bioavailability Promotion of the Food Bioactive Compounds: Nano Lipid Carriers Perspective - Amin Abbasi; Mohammad Hashemi; Hossein Samadi Kafil; Mohammadreza Abbasi Astamal; Masoud Lahouty; Anahita Ghorbani Tajani; Hedayat Hosseini; Seyedeh Zahra Nasirifar (Tabriz University of Medical Sciences, 2024)
Currently, a large number of people favor meals that are rich in nutraceuticals and phytochemical compounds, which help with the treatment or prevention of chronic diseases. Oral bioavailability is a crucial component of phytochemical bioefficiency, and endogenous mechanisms have a significant impact on how well nutraceuticals and phytochemicals are absorbed by the body. In addition to endogenous variables, exogenous factors that impact the bioavailability of bioactives include the food matrix, food processing, and food storage. Different delivery systems have evolved in this regard, and nanoscale delivery tools have also been created. Delivery methods that use nanostructured lipid carriers show benefits such as enhanced loading capacity, solubility, encapsulation effectiveness, storage stability, bioavailability, and half-life. They also provide safe food systems and regulated release. In this review, the outcomes of recent experimental reports are comprehensively reviewed. In addition, the food processing, storage, gut milieu circumstances, the release process from the food and nano delivery systems in the gastrointestinal tract (GIT) milieu, interactions with other GIT constituents, main delivery systems based on nanostructured lipid carriers for their encapsulation and eventually encapsulating technological barriers, food safety concerns, and regulatory issues of nutraceutical and phytochemical compounds are discussed.